Literasi matematika materi pembagian pada siswa kelas IV SD Negeri 72 Palembang - Intan Nur Azizah; Nyiayu fahriza Faudiah; Budi Utomo (IKIP Siliwangi, 2026)
This study aims to describe the mathematical literacy of fourth-grade students at SD Negeri 72 Palembang in the topic of division. A descriptive quantitative approach was used with 30 students as the research subjects. The instrument consisted of story-based math problems that were validated and tested for reliability. The results showed that students’ overall mathematical literacy was in the “fair” category, with an average score of 68.83. Specifically, 20% of students demonstrated very good ability, 26% good, 23.3% fair, and 30% low. Based on indicators, students’ ability to identify and formulate problems was relatively low (44%), while their ability to apply mathematical concepts or procedures (65%) and to explain solutions and interpret conclusions (62%) were in the fair category. These findings suggest that students’ mathematical literacy is not yet evenly distributed across all indicators and still needs improvement. Therefore, it is necessary to implement learning strategies that are more contextual, interactive, and focused on real-life problem solving, so students can develop mathematical literacy skills optimally and sustainably.